Produção biotecnológica de galacto-oligossacarídeos (GOS) a partir do soro do queijo porungo - Bolognesi, Lais Saldanha (2021)
The use of agro-industrial residues associated with enzymatic process technology has encouraged the development of new strategies for obtaining bioproducts, such as galactooligosaccharides (GOS). The β-galactosidase enzyme is widely used on production of lactose-free products and, recently, studies on the production of GOS have emerged to take advantage of the main residue of dairy industries – cheese whey. This is a substrate rich in lactose, contributing as an alternative and low-cost source for obtaining GOS, oligosaccharides that act as prebiotics. One way to obtain GOS is using the enzymatic immobilization technique, which allows for several advantages, including the reuse of the biocatalyst, the reduction of maintenance costs and the improvement of thermal stability. In this context, this project aimed to study the use of porungo cheese whey, a dairy product characteristic of the southwest of São Paulo, to produce GOS through the immobilized β-galactosidase enzyme. The work was divided into two moments, in which, in the first, two enzymatic immobilization strategies were evaluated (calcium alginate and calcium alginate-Concanavalin A) in relation to the optimum pH and temperature of the enzyme. In the second moment, obtaining GOS was tested using the most promising immobilization support on different substrates (lactose solution and cheese whey) and then from different concentrations of lactose added to porungo cheese whey (200 g L-1 to 400 g L-1) and temperatures (37 °C to 55 °C). Enzyme immobilization allowed us to verify an increase in the optimal pH range (7.0 to 7.5) for the calcium alginate support when compared to the free enzyme pH range (6.5), while for the calcium alginate support Calcium-Concanavalin A, a greater enzymatic activity was observed at lower pHs (6.0). With respect to temperature, a greater enzymatic activity was observed for the free enzyme in relation to the two immobilization supports tested. Higher GOS yields were observed in porungo cheese whey (63.2%) compared to the lactose solution (41.1%), which was used in the next step to evaluate the process conditions. The maximum GOS yield was 17.73%, with 61.4% lactose conversion, at 46 °C and 400 g L-1. These results suggest the possible use of porungo cheese whey as a substrate in the biotechnological production of GOS.